Komposisi dan Kepadatan Sampah Laut (Marine Debris) di Pulau Misool: Studi Kasus Pantai Salafen dan Waigama - Kolibongso, Duaitd; Alvianus, Sri Novia (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
Marine debris is widespread in oceans around the world, including in the most remote locations. Here, we conducted on the accumulation of macro debris on the Misool Island beach, an island ± 192 km away from the mainland of Sorong. The aim of the research is to examine compositions, densities, and accumulation rates of marine debris in two locations, namely Salafen and Waigama beaches at April-Mei 2023. The total amount of marine debris collected was 125 items during the survey conducted at two beaches with a total of 1.498 grams. The mean of densities marine debris is 0.12 ± 0.05 items/m2 and 1.49 ± 0.85 gr/m2 based on the weight. As much as 93% of the debris was marine debris categories plastics, followed by metals (3%), glass, and rubber as much as 2% respectively from a total of debris. The mean of debris accumulation rates showed the highest debris accumulations were found in Salafen beach (39.9 gr/days) than in Waigama beach (31.4 gr/days). Long-term monitoring is most important for more understanding of the path and temporal changes for the management of marine debris in the future.